ANALYSIS OF GINGEROL AND SHOGAOL COMPOUNDS FROM RED GINGER (ZINGIBER OFFICINALE VAR. RUBRUM) EXTRACT USING SEVERAL COMBINATIONS OF NATURAL DEEP EUTECTIC SOLVENT - YULIANITA; MUN’IM, ABDUL; YANUAR, ARRY; SAPUTRI, FADLINA CHANI (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of this research was to analyze the levels of gingerol and shogaol in red ginger (Zingiber officinale var. rubrum) extracted with different combinations of Natural Deep Eutectic Solvent (NADES) Methods: Red ginger was extracted using several combinations of NADES solvents, including Betaine: Citric Acid (1:2), Betaine: Malic Acid (1:1), Betaine: lactic Acid (1:2), Betaine: Tartaric Acid (1:1) and Betaine Oxalic Acid (1:1). The sieved ginger powder was added into 75 % v/v NADES in a solvent/solid ratio of 30/1. The mixture was ultrasonic extracted in an ultrasonic bath with an ultrasonic input power of 300 W and a frequency of 40 kHz under desired conditions. Analysis of the levels of gingerol and shogaol compounds in the extract was carried out using the validated High-Performance liquid Chromatography (HPLC) method. The method was validated by determining its specificity, linearity, accuracy, and precision. Results: The results showed that the combination of NADES between betaine: lactic acid (1:2) is the best solvent that can extract the highest total gingerol and shogaol with a level of 15.09 mg/g. Conclusion: The combination of NADES between betaine: lactic acid (1:2) can extract the highest total gingerol and shogaol compared to other NADES combinations.